Synthesis, structural characterization, and anti-ulcerogenic activity of schiff base ligands derived from tryptamine and 5-chloro, 5-nitro, 3,5-ditertiarybutyl salicylaldehyde and their nickel(II), copper(II), and Zinc(II) complexes - Mustafa, Iman Mohamed; Hapipah, Mohd Ali; Abdulla, Mahmood Ameen; Ward, T. Robinson (Elsevier, 2009)
Ni(II), Cu(II), and Zn(II) complexes with bidentate Schiff bases derived from the condensation reaction of 5-chlorosalicylaidehyde, 5-nitrosalicylaldehyde, and 3,5 ditertiarybutyl-2-hydroxy benzaldehyde with tryptamine, have been reported. The ligands and complexes were characterized by elemental analysis, IR, (1)H NMR and UV-Vis spectroscopy as well as single crystal X-ray structure analysis whenever possible. The complexes were found to have the general formula [M(L)(2)]. Spectral studies reveal that these Schiff bases were acting as bidentate ligands and co-ordinating to the metal center through deprotonated phenolate oxygen and azomethine nitrogen atoms. The Zn(II) complexes establish a tetrahedral geometry in a 1:2 metal to ligand stoichiometry, whereas a square planar geometry was proposed for the nickel and copper complexes, slightly distorted in the case of the latter. The antiulcer activity of 5-chlorosalicylalclehyde derivative and its nickel and copper complexes were evaluated in ethanol-induced gastric mucosal injury in rats. This Schiff base and its complexes promote ulcer protection as ascertained by the comparative decrease in ulcer areas, and inhibition of edema and leucocyte infiltration of the submucosal layer. (C) 2009 Elsevier Ltd. All rights reserved.